Reliability, sensitivity, and uncertainty of reservoir performance under climate variability in basins with different hydrogeologic settings in Northwestern United States. Issue 1 (2nd January 2017) - Mateus, Cristina; Tullos, Desiree
ABSTRACT: This study investigated how reservoir performance varied across different hydrogeologic settings and under plausible future climate scenarios. Modelling was conducted for the Santiam River Basin, OR, USA, comparing the North Santiam Basin, with high permeability and extensive groundwater (GW) storage, and the South Santiam Basin, with low permeability, little GW storage, and rapid runoff response. The coupling of projections of future temperature and precipitation from global climate models, a surface water–GW hydrologic model, and a formal Bayesian uncertainty analysis produced synthetic hydrographs of reservoir inflows. Inflow hydrographs were summarized as median and extreme future flows for inputs to a reservoir operations model. The performance of reservoir operations was evaluated as the failure to meet flood management, spring and summer environmental flows, and hydropower generation objectives. Despite projected increases in winter flows and decreases in summer flows, results provided little evidence of a response in reservoir operation performance to a changing climate, with the exception of summer flow targets. Independent of climate impacts, historical prioritization of reservoir operations played an important role in the reliability of flood regulation, demonstrating the importance of reservoir operations relative to hydrologic responses to climate change in this basin. Results also highlight how hydrologic uncertainty is likely to complicate planning for climate change in basins with substantial GW interactions.